Rhotics.New Data and Perspectives - Beňuš, Štefan (bu,press, 2013)
This book provides an insight into the patterns of variation and change of rhotics in different languages and from a variety of perspectives. It sheds light on the phonetics, the phonology, the socio-linguistics and the acquisition of /r/-sounds in languages as diverse as Dutch, English, French, German, Greek, Hebrew, Italian, Kuikuro, Malayalam, Romanian, Slovak, Tyrolean and Washili Shingazidja thus contributing to the discussion on the unity and uniqueness of this group of sounds.